1998
DOI: 10.1103/physrevb.58.9867
|View full text |Cite
|
Sign up to set email alerts
|

Diffusion by bond hopping of hydrogen atoms on the Si(111)-7×7 surface

Abstract: Site-specific adsorption and diffusion of atomic hydrogen on the Si͑111͒-7ϫ7 surface at elevated temperatures are studied by scanning tunneling microscopy. Hydrogen atoms are found to adsorb preferentially on rest-atom sites rather than adatom sites with a binding-energy difference of ϳ0.2 eV. The adsorption causes a reverse charge transfer from rest atoms back to adatoms. Above ϳ280°C, atomic hopping between two rest-atom sites within a half-cell can occur which is mediated by an adatom site. Above ϳ330°C, H … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(29 citation statements)
references
References 34 publications
4
24
1
Order By: Relevance
“…From filled-state images, the adsorption of H atom on a rest atom site was found to enhance the brightness of the three neighboring unreacted adatoms, not seen in the empty-state images. 38 In our work, one adatom adjacent to the reacted rest atom is darkened upon reaction. The remaining two unreacted adatoms indeed become brighter.…”
Section: Scanning Tunneling Microscopic Studymentioning
confidence: 88%
“…From filled-state images, the adsorption of H atom on a rest atom site was found to enhance the brightness of the three neighboring unreacted adatoms, not seen in the empty-state images. 38 In our work, one adatom adjacent to the reacted rest atom is darkened upon reaction. The remaining two unreacted adatoms indeed become brighter.…”
Section: Scanning Tunneling Microscopic Studymentioning
confidence: 88%
“…Usually, the diffusion of atoms on low-index surfaces is two dimensional and rather isotropic, like in the case of various adsorbates on the Si(111) surface [7][8][9][10][11][12][13][14][15][16][17][18][19][20][21][22]. However, the movement of atoms can become strongly anisotropic or even quasi-one-dimensional in the presence of a specific surface reconstruction or on stepped (vicinal) templates [23][24][25][26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…It was found that the Si adatoms of the (7×7) structure are the preferential sites for H adsorption at low coverage. In contrast, high-temperature STM studies of H/Si(111)7×7 have shown that the rest atoms acted as preferential adsorption sites and it was argued that the room temperature results might not correspond to the thermodynamically stable final state [9,10]. One issue of this work is devoted to this controversy more specifically by adsorption experiments both at room and at elevated temperature.…”
Section: Introductionmentioning
confidence: 84%
“…Note that for better visibility of adsorption on rest atoms a negative value of the sample bias must be applied [9,10]. It is evident from the images, however, that reaction of the Si adatoms with H occurs from the beginning of the adsorption experiments at both room and elevated temperatures.…”
Section: Initial Stages Of H Adsorption At Room and Elevated Temperatmentioning
confidence: 95%
See 1 more Smart Citation